2011
DOI: 10.1007/s10751-011-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Spin re-orientation in FeCr2S4

Abstract: The spinel FeCr 2 S 4 has been studied intensely for its peculiar magnetic and local structural changes which are sensitively influenced by the Jahn-Teller properties of Fe 2+ in tetrahedral sulfur coordination. Recent muon spin rotation data give strong evidence that the commonly assumed collinear magnetic structure of this compound is only found between the Curie temperature T C = 165 K and 50 K. For lower temperatures a helical structure has been proposed. We present new Mössbauer spectroscopic data taken o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…This temperature coincides with the temperature T M where a transition from a collinear to a non-collinear spin configuration with three different Fe sites has been reported by µSR and where orbital fluctuations are assumed to set in. [12,26,27] The relative change of the thermal expansion upon entering the ground state below 10 K is similar to the zero-field data, but under applied fields of 6 T and 12 T the sample expands again towards lowest temperatures. This is clearly seen in the negative thermal expansion coefficient for the transition in magnetic fields.…”
Section: Neutron Diffractionsupporting
confidence: 70%
See 1 more Smart Citation
“…This temperature coincides with the temperature T M where a transition from a collinear to a non-collinear spin configuration with three different Fe sites has been reported by µSR and where orbital fluctuations are assumed to set in. [12,26,27] The relative change of the thermal expansion upon entering the ground state below 10 K is similar to the zero-field data, but under applied fields of 6 T and 12 T the sample expands again towards lowest temperatures. This is clearly seen in the negative thermal expansion coefficient for the transition in magnetic fields.…”
Section: Neutron Diffractionsupporting
confidence: 70%
“…[7,[12][13][14][15][16][17][18][19] In addition, an anomaly in the lowfield magnetization at T M = 60 K revealed a change in the magnetic configuration, [12,[20][21][22][23][24][25] which has recently been attributed to the formation of a non-collinear (possibly helical) spin configuration with an incommensurate modulation involving three different Fe sites as indicated by µSR, Mössbauer, and time-resolved magneto-optical Kerr effect measurements. [26][27][28] The same temperature has also been associated with the onset of short-range orbital order (orbital liquid) and dynamic JT distortions, suggesting a mutual influence of spin configuration and orbital correlations. [12] At room temperature FeCr 2 S 4 crystallizes in the spinel structure with space group F d 3m with eight formula units per unit cell.…”
Section: Introductionmentioning
confidence: 93%
“…A major progress in understanding the low-temperature magnetic behaviour was provided by µSR experiments [30] which established a transformation of the collinear ferrimagnetic structure into an incommensurate (possibly helical) structure below 50 K, which remains the stable spin configuration in the ground state. Recent Mössbauer studies [31] found three non-equivalent Fe sites appearing below 50 K which corroborates the µSR results regarding the change of the spin structure from collinear to a helical one. To get further insight into the intriguing physics of FeCr 2 S 4 we utilized ultrasound spectroscopy using a propagation techniques which are known to be very sensitive for detecting spin, orbital and structural correlations [32].…”
Section: Introductionsupporting
confidence: 86%